2022
DOI: 10.24200/sci.2022.57298.5164
|View full text |Cite
|
Sign up to set email alerts
|

Generalized Variance Estimator using Auxiliary Information in the Presence and Absence of Measurement Error

Abstract: In this study, we have proposed a new generalized estimator using auxiliary information for the estimation of population variance in presence and absence of measurement error. The expressions approximate bias and mean square error of the proposed generalized estimator are derive up to the first-order. Several new and existing estimators are found as the special cases of proposed estimator and expressed on various values of optimizing and generalized constants. The proposed estimator is compared mathematically … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 21 publications
(27 reference statements)
0
6
0
Order By: Relevance
“…Without taking the MEs into consideration, the estimates seem incomplete which misleads the inference of the study. Various authors including Shalabh 7 , Manisha and Singh 8 , Singh and Karpe 9 13 , Diana and Giordan 14 , Gupta et al 15 , Tariq et al 16 , 17 and Singh et al 18 have focused on the estimation of various parameters such as population mean, total, ratio, product and variance under MEs.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Without taking the MEs into consideration, the estimates seem incomplete which misleads the inference of the study. Various authors including Shalabh 7 , Manisha and Singh 8 , Singh and Karpe 9 13 , Diana and Giordan 14 , Gupta et al 15 , Tariq et al 16 , 17 and Singh et al 18 have focused on the estimation of various parameters such as population mean, total, ratio, product and variance under MEs.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the resulting modified correlated MEs model is:with |α| < 1 and |η| < 1.Here we note that α and η may take the values of ρ YX and ρ uv as |ρ YX | < 1 and |ρ uv | < 1. Now we define the ratio ( t * R ) and product ( t * P ) estimators for population mean µ Y of Y under the model(17) asTo study the properties of the estimators t…”
mentioning
confidence: 99%
“… [6] discussed the estimation of population variance under MEs. [7] and [8] suggested some population variance estimation methods utilizing supplementary data in the absence and presence of MEs. [9] , [10] , [11] evaluated the performance of several classes of estimators under the impact of the correlated MEs.…”
Section: Introductionmentioning
confidence: 99%
“…Hussain et al [9] suggested the estimation of a fnite population distribution function with the dual use of supplementary information under nonresponse. Tariq et al [10] proposed a supplementary information-based variance estimator to tackle the problem of ME. Tariq et al [11] suggested a generalized variance estimator utilizing supplementary information in the presence and absence of ME.…”
Section: Introductionmentioning
confidence: 99%
“…Tariq et al [10] proposed a supplementary information-based variance estimator to tackle the problem of ME. Tariq et al [11] suggested a generalized variance estimator utilizing supplementary information in the presence and absence of ME. Zahid et al [12] developed a generalized class of estimators for the sensitive variables in the case of ME and nonresponse.…”
Section: Introductionmentioning
confidence: 99%